2015
DOI: 10.5588/ijtld.14.0262
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the Xpert® MTB/RIF assay for extra-pulmonary tuberculosis: a meta-analysis

Abstract: Xpert has high specificity but limited sensitivity for the detection of EPTB. Although positive Xpert test results may be useful in rapidly identifying EPTB cases, negative test results provide less certainty for ruling out disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 0 publications
7
70
3
1
Order By: Relevance
“…Notably, the impact of sample type,[21,22] age of patients,[12] and status of HIV co-infection [23] and smear-positivity [24] are the main factors studied for their impact on Xpert MTB/RIF’s diagnostic accuracy. In this context, our results showed that Xpert MTB/RIF has higher sensitivity in patients with positive smears (0.99, 95% CI 0.97–0.99), in patients with PTB samples (0.87, 95% CI 0.83–0.90), in adults (0.82, 95% CI 0.76–0.86) and in HIV-positive patients (0.81, 95% CI 0.73–0.87).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the impact of sample type,[21,22] age of patients,[12] and status of HIV co-infection [23] and smear-positivity [24] are the main factors studied for their impact on Xpert MTB/RIF’s diagnostic accuracy. In this context, our results showed that Xpert MTB/RIF has higher sensitivity in patients with positive smears (0.99, 95% CI 0.97–0.99), in patients with PTB samples (0.87, 95% CI 0.83–0.90), in adults (0.82, 95% CI 0.76–0.86) and in HIV-positive patients (0.81, 95% CI 0.73–0.87).…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] Recently, a meta-analysis reported the pooled sensitivity and specificity of Xpert MTB/RIF to be 37% and 92%, respectively, in TB pleurisy. [35] The paucibacillary nature of pleural specimens was considered to be the main reason for this. Therefore, we assume that immunologic diagnosis using M. tuberculosis-specific T-cells will play a more important role than molecular or culture-based methods in patients with suspected TB pleurisy.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Data on Xpert performance in CSF in adults are limited to reports of small numbers of meningitis patients in extra-pulmonary TB cohorts 10–18 , multiple meta-analyses 9,19,20 , and two well-conducted TBM cohort studies. 21,22 In South Africa, Patel et al found 67% sensitivity with Xpert in microbiologically proven TBM.…”
Section: Introductionmentioning
confidence: 99%